Neurophysiology of gait: From the spinal cord to the frontal lobe - Takakusaki, Kaoru (Movement disorders, 2013)
ABSTRACT Locomotion is a purposeful, goal‐directed behavior initiated by signals arising from either volitional processing in the cerebral cortex or emotional processing in the limbic system. Regardless of whether the locomotion initiation is volitional or emotional, locomotion is accompanied by automatic controlled movement processes, such as the adjustment of postural muscle tone and rhythmic limb movements. Sensori‐motor integration in the brainstem and the spinal cord plays crucial roles in this process. The basic locomotor motor pattern is generated by spinal interneuronal networks, termed central pattern generators (CPGs). Responding to signals in proprioceptive and skin afferents, the spinal interneuronal networks modify the locomotor pattern in cooperation with descending signals from the brainstem structures and the cerebral cortex. Information processing between the basal ganglia, the cerebellum, and the brainstem may enable automatic regulation of muscle tone and rhythmic limb movements in the absence of conscious awareness. However, when a locomoting subject encounters obstacles, the subject has to intentionally adjust bodily alignment to guide limb movements. Such an intentional gait modification requires motor programming in the premotor cortices. The motor programs utilize one's bodily information, such as the body schema, which is preserved and updated in the temporoparietal cortex. The motor programs are transmitted to the brainstem by the corticoreticulospinal system, so that one's posture is anticipatorily controlled. These processes enable the corticospinal system to generate limb trajectory and achieve accurate foot placement. Loops from the motor cortical areas to the basal ganglia and the cerebellum can serve this purpose. © 2013 International Parkinson and Movement Disorder Society